Effect of gasification agent on co-gasification of rice production wastes mixtures. (15th September 2016) - Pinto, Filomena; André, Rui; Miranda, Miguel; Neves, Diogo; Varela, Francisco; Santos, João
Highlights: Co-gasification of biomass rice wastes blended with polyethylene (PE). Use of mixtures of air, oxygen steam and CO2 with different compositions of two or more components as gasification agent. Study of CO2 -blown gasification. Effect of gasification agent on the release of H2 S and NH3 . Abstract: Rice production generates different types of wastes, rice husk and straw and plastics, mainly polyethylene (PE) used in bags for rice packaging and for seeds and fertilizers transport. Due to their contamination they are not suitable for physical recycling and end-up in landfills. Biomass rice wastes may have some utilisations, but each of them has drawbacks. This paper studies the possibility of using fluidised bed co-gasification of all these wastes for their energetic valorisation. Gasification gas composition and heating value is affected by the gasification and fluidisation agent. Mixtures of air, oxygen, steam and CO2 with different compositions of two or more components were tested. Besides the high cost of producing oxygen, the results obtained showed that the best technical option was the use of steam and oxygen, because the gas was not diluted in nitrogen and thus gas HHV (higher heating value) on dry basis increased around 42%. However, the use of enriched air with up to 40% (v/v) of oxygen may be an alternative, due to the lower cost of producing this gas and also because better results were obtained than those for air-blown gasification. The use of CO2 as gasification and fluidisation agent may be a good route, as the results obtained showed that CO2 reforming reactions were promoted. The increase of CO2 content in gasification agent led to a decrease of 45% in tar content, which was followed by a great increase in gas yield, around 70%. The main drawback of using steam and CO2 is the need to supply the energy for the endothermic reactions, hence a good option could be the use of mixtures of CO2, O2 and steam as gasification agent.